The Theoretical Description for Cenobamate CuS-Assisted Electrochemical Determination in Pharmaceutical Formulations and Wastewater - Volodymyr Tkach; Tetiana Morozova; Viktoriia Khrutba; Andrii Hlukhonets; Marta Kushnir; Yana Ivanushko; Viktor Kryvetskyi; Inna Kryvetska; Igor Kryvetskyi; Petro Yagodynets; Mykhailo Kucher; Zholt Kormosh; et al. (Orbital: The Electronic Journal of Chemistry, 2024)
For the first time, the theoretical description for cenobamate antiepileptic drug on anode, assisted by copper sulfide nanoparticles in alkaline medium, has been given. Two mechanisms, involving either tetrazolic ring, or the carbocyclic aromatic moiety, are possible for this process, reason why the concentration of the drug will be identified and quantified by two peaks. Despite of the mechanism hybrid nature, both of the peaks will produce an easy interpretable analytical signal, being thereby possible to confirm the efficiency of the electroanalytical signal.